> 数学 >
乘法公式的几道题!
化简:
(-x-1)(x^2-x+1)的结果是( )
a.-x^3+1 b.-x^3-1 c.x^3+1 d.x^3-1
(a^2-a+1)(a^2+a+1)(a^4-a^2+1)
(x^2-y^2)(x+y)-2xy(x-y)(x+y)
(a+b+c)^2-(b+c)^2-(c+2)^2-(a+b)^2
(x^5-x^2)(x^10+x^7+x^4)
人气:174 ℃ 时间:2020-02-03 13:58:47
解答
(1) B
(-x-1)(x^2-x+1)=-(x+1)(x^2-x+1)=-(x^3+1)=-x^3-1
(2)(a^2-a+1)(a^2+a+1)(a^4-a^2+1)
=(a^2+1-a)(a^2+1+a)(a^4-a^2+1)
=[(a^2+1)^2-a^2](a^4-a^2+1)
=(a^4+a^2+1)(a^4-a^2+1)
=(a^4+1)^2-(a^2)^2
=a^8+a^4+1
(3)(x^2-y^2)(x+y)-2xy(x-y)(x+y)
=(x+y)(x-y)(x+y-2xy)
(4)(a+b+c)^2-(b+c)^2-(c+a)^2-(a+b)^2
=a(a+2b+2c)-(c+a)^2-(a+b)^2
=a^2+2ab+2ac-c^2-2ac-a^2-a^2-2ab-b^2
=-c^2-a^2-b^2
(5)(x^5-x^2)(x^10+x^7+x^4)
=x^6(x^3-1)(x^6+x^3+1)
=x^6(x^9-1)
=x^15-x^6(3楼这错了吧)
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版